K. Jaspers and Social-Theoretical Premises of Existentialism - Repšys, Jonas (Problemos, 1972)
The article presents some notes on K. Jaspers’s biography. On the basis of an analysis of the monopolist stage of imperialism, technological progress, its social consequences and specific features of spiritual culture, the author throws light on social and theoretical premises of the formation of existentialism. Against the background of confronting positive scientism with irrationalism, some distinquishing features of K. Jaspers’ philosophy are presented.